The impact of attachment styles and peer pressure on risk taking behavior in adolescents - SATAN, AYŞİN (My University, 2022)
The purpose of this research is to examine the effects of attachment styles and peer pressure on risk taking behaviors in adolescents. The research was carried out within the scope of the screening model, which is one of the descriptive research methods. The universe of the research is students from the High Schools in Istanbul. The sample of the study was consisted of 340 students which were selected by simple random sampling method. 191 of these students were female (56.2%) and 149 were male (43.8%). Relation Scale, Peer Print Scale and Risk Taking Behavior scale were used in the research. The Pearson Moments Multiplication Correlation coefficient was used to see the relationship between attachment styles, peer pressure, and risk taking behaviors in the study. Then, hierarchical regression analysis was used for the related variables. Results showed that, in the first step; peer pressure explains 16% of the risk taking behavior alone, while in the second step; secure attachment style from the attachment styles explains 3% of the risk taking behavior and in the third step; the obsessive attachment style from the attachment styles explains 2% of the risk taking behavior. In the direction of these findings it is seen that, risk taking behavior is more explained by peer pressure variable than by other variables.

Bu araştırmanın amacı ergenlerde bağlanma stilleri ve akran baskısının risk alma davranışı üzerindeki etkisinin incelenmesidir. Araştırma betimsel araştırma yöntemlerinden tarama modeli kapsamında yürütülmüştür. Araştırmanın evreni İstanbul’da lisede okuyan öğrencilerdir. Evrendeki öğrencilerden seçkisiz örnekleme yönteminden basit seçkisiz örneklemeyle seçilen 340 öğrenci araştırmanın örneklemini oluşturmaktadır. Bu öğrencilerin 191’i kız ( % 56.2) 149’su erkektir (% 43.8). Araştırmada İlişki Ölçeği, Akran Baskısı Ölçeği ve Risk Alma Davranışı Ölçeği kullanılmıştır. Araştırmada bağlanma stilleri, akran baskısı ve risk alma davranışları puanları arasındaki ilişkiyi ölçmek için Pearson Momentler Çarpımı Korelasyon katsayısı kullanılmıştır. Daha sonra aralarında ilişki bulunan değişkenlere Hiyerarşik Regresyon analizi uygulanmıştır. Yapılan analiz sonucunda ilk adımda akran baskısı, risk alma davranışının tek başına %16’sını açıklarken ikinci adımda bağlanma stillerinden güvenli bağlanma stili %3’ünü ve üçüncü adımda bağlanma stillerinden saplantılı bağlanma stili ise %2’sini açıklamaktadır. Araştırma bulguları doğrultusunda risk alma davranışını akran baskısı değişkeninin diğer değişkenlere göre daha fazla açıkladığı görülmektedir.
Ergenlik döneminde risk alma davranışının yordayıcıları olarak akran baskısı ve bağlanma stillerinin incelenmesi
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Eğitim Bilimleri; Social Sciences and Humanities; Education; Educational Sciences; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Attachment Styles; Peer Pressure; Risk Taking Behavior; Bağlanma Stilleri; Akran Baskısı; Risk Alma Davranışı